A Study on Urinary Tract Infection and Metabolic Diseases in Stone Patients (Medical Forum Monthly, 2021)
Objective: The main objective of the study is to analyze the Urinary Tract Infection and metabolic diseases in Stone Patients among local population of Sialkot.Study Design: Cross Sectional StudyPlace and Duration of Study: This study was conducted at the Allama Iqbal Memorial Teaching Hospital, Sialkot during June 2018 to June 2019.Materials and Methods: The definite history of the multitude of patients were accumulated and 24 hour p-test was gathered from every patient and sent for PH, explicit gravity, Creatinine, uric corrosive, calcium, phosphate, oxalate, citrate and magnesium. 24 hour p-tests were gathered in plastic boxes, which don't respond artificially by standard techniques, and were put away at 2-8ºC. Likewise, blood test of every patient was additionally sent for serum levels of urea, creatinine, uric corrosive, phosphate and calcium.Results: The data were collected from 100 patients with the mean age 38 ± 7.75 years. There were 35 male and 65 female patients who were selected this investigation. The primary introducing grievance was amble torment on the influenced side for example in 79.0% patients, trailed by hematuria and consuming micturition. Dominant part of the patients for example 94.0%, were analyzed as having renal stone or ureteric stone.Conclusion: It is concluded that recurrence of metabolic variations from the norm is exceptionally high in patients with urolithiasis and hyperoxaluria, hypercalciuria and hypocitraturia are the main metabolic irregularities saw in these patients. Stone sickness is an expanding and significant general health issue with high recurrence of bladder stone.